Autoimmune heparin‐induced thrombocytopenia of delayed onset: a clinical challenge. Issue 12 (4th October 2018) - Kuitunen, Anne; Sinisalo, Marjatta; Vahtera, Annukka; Hiltunen, Leena; Javela, Kaija; Laine, Outi
Abstract : BACKGROUND: Heparin‐induced thrombocytopenia (HIT) usually appears at 5 to 10 days after initiation of heparin. Autoimmune HIT can arise after discontinuation of heparin treatment (delayed‐onset HIT) or without any preceding heparin exposure (spontaneous HIT syndrome). CASE REPORT: This case presents a course of autoimmune HIT with delayed onset. The patient was hospitalized due to influenza pneumonia and received low‐molecular‐weight heparin thromboprophylaxis for 9 days. Seven days after discharge, she was readmitted because of a cerebral sinus vein thrombosis and severe thrombocytopenia. Intracranial bleeding and brain infarction caused her death. DISCUSSION: Autoimmune HIT was confirmed by functional heparin‐induced platelet (PLT) activation test. Intracranial bleeding prevented continuous and effective anticoagulation. PLT transfusions were given, although they are generally advised against in HIT patients due to potential risk of thromboembolic events. CONCLUSION: This case presents that testing PLT‐activating antibodies both in the presence and in the absence of current heparin treatment helps to diagnose patients with autoimmune HIT. There is conflicting evidence to refuse PLT transfusion when HIT is complicated with life‐threatening bleeding.